"GREEN REVOLUTION: THE AGRARIAN TRANSFORMATION OF JAMMU AND KASHMIR FROM THE 19TH TO 20TH CENTURY" - Prince Raina; Dr. Dinesh Mandot (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The agrarian history of Jammu and Kashmir reflects a significant transformation driven by the Green Revolution, which spanned from the 19th to the 20th century. This paper explores the multifaceted impact of agricultural advancements on the socio-economic fabric of the region. By examining historical records, agricultural practices, and socio-political changes, this study highlights the profound shifts in productivity, land use, and rural livelihoods brought about by the Green Revolution in Jammu and Kashmir.